X‐ray computed tomography: Morphological and porosity characterization of giant Antarctic micrometeorites. (23rd June 2020) - Dionnet, Zelia; Suttle, Martin D.; Longobardo, Andrea; Rotundi, Alessandra; Folco, Luigi; Della Corte, Vincenzo; King, Andrew
Abstract: Giant micrometeorites (MMs; 400–2000 µm) are exceedingly rare and scientifically valuable. Three‐dimensional nondestructive characterization by X‐ray computed tomography (X‐CT) provides information on the petrography and thus petrogenesis of MMs and serves as a guide to maximize subsequent multi‐analytical studies on such precious planetary materials. Here, we discuss the results obtained by X‐CT on 22 giant MMs and the classification based on their 3‐D density contrast images. Scoriaceous and unmelted MMs have distinct porosity ranges (10–40 vol% versus 0–25 vol%, respectively). We observe a porosity variation inside scoriaceous MMs, which allows their atmospheric entry flight history to be resolved. For the first time, spinning entry is explicitly demonstrated for four partially melted MMs. Furthermore, we are able to resolve the thermal gradient in a single particle, based on porosity variation (seen as a progressive increase in pore abundance and size with higher peak temperatures). Moreover, we explore parent body alteration through the 3‐D analysis of pores distribution, showing that shock fabrics are either absent or weakly developed in our data set. Finally, owing to the detection of pseudomorphic chondrules, we estimate that the intensively aqueously altered C1 or CI‐like material could represent 18% of the MM flux at this size fraction (400–1000 µm).